2020
DOI: 10.1371/journal.pone.0240596
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis of dietary restriction in Drosophila

Abstract: To explore the underlying mechanism of dietary restriction (DR) induced lifespan extension in fruit flies at protein level, we performed proteome sequencing in Drosophila at day 7 (young) and day 42 (old) under DR and ad libitum (AL) conditions. A total of 18629 unique peptides were identified in Uniprot, corresponding to 3,662 proteins. Among them, 383 and 409 differentially expressed proteins (DEPs) were identified from comparison between DR vs AL at day 7 and 42, respectively. Bioinformatics analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Low energy intake was strongly associated with processes involved in RNA metabolism, particularly splicing and the spliceosome. This has been noted recently in standard caloric restriction models in C. elegans (Heintz et al, 2017), D. melanogaster (Gao et al, 2020), mice (Swindell, 2009), and monkeys (Rhoads et al, 2018;Rhoads et al, 2020). In the monkey study it was concluded that upregulation of splicing indicates that alternate transcripts regulate the broad response to energy depletion (Rhoads et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Low energy intake was strongly associated with processes involved in RNA metabolism, particularly splicing and the spliceosome. This has been noted recently in standard caloric restriction models in C. elegans (Heintz et al, 2017), D. melanogaster (Gao et al, 2020), mice (Swindell, 2009), and monkeys (Rhoads et al, 2018;Rhoads et al, 2020). In the monkey study it was concluded that upregulation of splicing indicates that alternate transcripts regulate the broad response to energy depletion (Rhoads et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…An association between the spliceosome and caloric restriction has been reported in C. elegans (Heintz et al, 2017), D. melanogaster (Gao et al, 2020) mice (Swindell, 2009) and Rhesus monkeys (Rhoads et al, 2018;Rhoads et al, 2020). In monkeys, caloric restriction was achieved by providing the monkeys with 30% less food than ad libitum-fed monkeys and this led to increased lifespan (Colman et al, 2009).…”
Section: Low Energy Intake Upregulates the Spliceosomementioning
confidence: 96%
“…Transcriptional analysis identifies phases of response to DR beginning with activation of oxidative metabolism; followed by stress signaling and lipid metabolism; and then autophagy, stress, and the metabolic switch to increased expression of FAO and gluconeogenic genes (Romey-Glu ¨sing et al, 2018). Proteomic analysis of whole flies reveals subtle differences in the response to DR depending on the age of the animals (Gao et al, 2020).…”
Section: Fliesmentioning
confidence: 99%
“…Studies examining the effects of DR on expression of proteins (e.g. Gao et al, 2020), especially if combined with manipulation of ambient temperature, could provide additional clues on how dietary protein requirements for homeostasis and somatic maintenance are altered by thermal stress.…”
Section: Male Mating Behaviourmentioning
confidence: 99%